Mobility, meaning and the transformations of things shifting contexts of material culture through time and space - Hahn, Hans Peter; Weiss, Hadas (Oxford, UK Oxbow Books, 2013)
Things travel around the globe: they are shipped as mass consumer goods, or transported as souvenirs or gifts. There are infinite ways for things to be mobile, not only in the era of globalisation but since the beginning of time, as the earliest traces of long distance trading show. This book investigates the mobility of things from archaeological and anthropological perspectives. Material Objects are characterised by temporal continuity, embodying a prior existence with lingering effects. Yet the material continuity disguises the transformations they may undergo, which only become evident upon closer examination. Objects are in perpetual flux, leaving visible traces of their age, usage, and previous life. While travelling through time, objects also circulate through space, and their spatial mobility alters their meaning and use with respect to new cultural horizons. As objects transform through time and space, so does the value attributed to them. Mapping out itineraries of value in the realm of the material, allows us to grasp the nature of a given social formation through the shape and meaning taken on by its valued'stuff'. It also provides insights into the nature of materiality, through the value ascribed to objects at a given point in time and space. This edited volume brings together studies of material culture, materiality and value, with regard to the mobility of objects, with the aim of tracing the ways in which societies constitute their valued objects and how the realm of the material reflects upon society.
Includes index.
Keywords: Material culture -- Case studies; Material culture -- Congresses; Electronic books